On the question of the classification of Ukrainian sociological terminology - Синєгуб, Ярослава Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
This article is an attempt to substantiate the principles of the thematic classification of Ukrainian sociological terms, defining the principles of their systematic ordering. The article highlights and analyzes 9 thematic groups for the designation of sociological names. The notion of lexical-semantic and thematic group is distinguished. In branch terminology sociological terms denote elements, attitudes and features of the corresponding terminology system. They can be divided into a number of generalized thematic names of categorical scientific concepts: phenomena, processes, attributes, properties, abilities. The selected thematic groups of the studied terms are the most typical representatives of the systematic ordering of Ukrainian sociological terminological units, whose meaningful categorization is subordinated to the general laws of the language. The Ukrainian sociological terminology system, as well as any other industry terminology, is open and dynamic, as evidenced by the activity of the emergence of new terminology on the designation of relevant industry concepts.